International Political Economy and Poststructural Politics
XI, 278 p.
Keywords: This edited volume brings together leading scholars to debate the promises of poststructural politics within the study of the International Political Economy (IPE). The volume offers a sustained theoretical dialogue on the meaning of discourse, identity, and representation for practices of political economy.